Phenotypic variation in LADD syndrome. Issue 5 (October 1985) - Thompson, E; Pembrey, M; Graham, J M
Abstract : A mother and son are reported with chronic dacrocystitis, cup shaped ears, hearing loss, abnormal teeth, and poor formation of saliva and tears. They are similar to previously reported cases of lacrimo-auriculo-dento-digital (LADD) syndrome. The variability of expression of this autosomal dominant syndrome is discussed, and it is suggested that poor saliva and tear formation be added to the phenotype.